2020
DOI: 10.21203/rs.3.rs-60500/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Economic Burden of Coronavirus Disease 2019 (COVID-19): Evidence from Iran

Abstract: This study aimed to estimate both direct medical and indirect costs of treating the Coronavirus disease 2019 (COVID-19) from a societal perspective in the patients at a referral hospital in Fars province as well as the economic burden of COVID-19 in Iran in 2020.Methods:This is a partial economic evaluation and a cross-sectional cost-description study conducted descriptively-analytically and based on the data of the COVID-19 patients referred to a referral university hospital in Fars province between March and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
49
3
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 17 publications
4
49
3
3
Order By: Relevance
“…The total indirect and direct costs were estimated at 5450.66 and 3362.49 PPP, respectively. Our results are consistent with a previous study in Iran, in which the total mean indirect and direct medical costs were estimated to be $ 11,634 and $3755, respectively ( 21 ). Kim et al performed a study to determine cost breakdowns associated with the 2009 pandemic H1N1 influenza in Korea (2013).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The total indirect and direct costs were estimated at 5450.66 and 3362.49 PPP, respectively. Our results are consistent with a previous study in Iran, in which the total mean indirect and direct medical costs were estimated to be $ 11,634 and $3755, respectively ( 21 ). Kim et al performed a study to determine cost breakdowns associated with the 2009 pandemic H1N1 influenza in Korea (2013).…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the main components of the total indirect costs were caused by missed workdays (88%), followed by premature death (12%). In contrast, in another study in Iran, income loss due to premature death was the main component of indirect costs ($10,190), followed by job absenteeism during the recovery course ($1065) and economic production loss due to hospitalization ($378) ( 21 ). Additionally, we found that direct non-medical costs accounted for a small proportion of total indirect costs (1.7%).…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations